List : a novel - Roberson, Matthew (FC2, 2014)
Vignettes of a middle-class American family told through lists, each reflecting their obsessions, their complaints, their desires, and their humanity. A suburban family of four- a man, woman, boy, and girl- struggle through claustrophobic days crowded with home improvement projects, conflicts at work and school, a job loss, illnesses, separation, and the wearying confrontation with aging. The accoutrements of modern life- electronic devices and vehicles- have ceased to be tools that support them and have become instead the central ful.